Empresas transnacionais e direitos humanos: uma abordagem pragmática da responsabilidade social baseada em códigos de conduta coletivos - Righi, Lucas Martins (2016)
The Global society has as one of its main features the transnationalisation of the capitalist economic activity, a phenomenon represented by the opening of branches abroad, the acquisition of controlling interest of commercial companies from other States, the business merger, the formation of groups and joint ventures or contracting suppliers in areas with lower labor and legal costs. However, the economic results are accompanied by negative social outcomes, among which occur violations of human rights of workers and communities, which was particularly denounced from the 70s of XX century. This problem of globalization has not been approached by an international treaty that would create binding legal obligations for transnational corporations in relation to human rights; at the same time, the social actors themselves have taken voluntary commitments recognizing their responsibilities in improving the social impact of their cross-border economic activities, it is called corporate social responsibility. Because of the proliferation of these social standards through the so-called conduct codes, individual or collective, challenging the classical categories of Law, it is necessary to study them based on the following problem: the corporate social responsibility based on collective codes of conduct generates relevant material effects to increase corporate respect for human rights globally? To address the matter it was employed the pragmatic approach advocated by the researchers of Law Philosophy of Perelman Center in its "Global Law" program. In addition, the survey was complemented by the use of the historical and monographic procedure methods (five collective conduct codes of global scope), with indirect documentary research technique with bibliographical and documentary research. Relevant material effects were found, as opportunities for improvement the preventive control of business conduct, but also negative aspects considered as implicit threats to control sitemas concerned.